2020
DOI: 10.1088/1361-6560/abb7c1
|View full text |Cite
|
Sign up to set email alerts
|

Role of skin tissue layers and ultra-structure in transcutaneous electrical stimulation including tDCS

Abstract: Background. During transcranial electrical stimulation (tES), including transcranial direct current stimulation (tDCS) and transcranial alternating current stimulation (tACS), current density concentration around the electrode edges that is predicted by simplistic skin models does not match experimental observations of erythema, heating, or other adverse events. We hypothesized that enhancing models to include skin anatomical details, would alter predicted current patterns to align with experimental observatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 96 publications
0
22
0
Order By: Relevance
“…Furthermore, recent studies have suggested that several other individual anatomical factors (e.g. absolute head volume and relative volume of skin, skull and CSF [56], as well as anatomical details of the skin [57]) are relevant for the tDCS-induced EF. Conceptually, EF, and especially the normal component of EF, which takes into account directional differences of EF due to stimulation polarity, should be better suited to predict physiological tDCS effects than single anatomical factors, because it is based on the contribution of all potentially relevant anatomical factors.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…Furthermore, recent studies have suggested that several other individual anatomical factors (e.g. absolute head volume and relative volume of skin, skull and CSF [56], as well as anatomical details of the skin [57]) are relevant for the tDCS-induced EF. Conceptually, EF, and especially the normal component of EF, which takes into account directional differences of EF due to stimulation polarity, should be better suited to predict physiological tDCS effects than single anatomical factors, because it is based on the contribution of all potentially relevant anatomical factors.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…Current passage through the scalp (skin) depends on numerous layers and ultra-structures, each with a complex (non-linear, time-dependent) impedance to current flow [16,[38][39][40][41][42] which is computationally intractable for tES head models [21]. The pipeline developed here to simulate adaptive-scalp conductivity during tES represent two scalp layers, with just two respective associated subject-specific parameters: a deep-scalp layer with fixed conductivity (σ #! )…”
Section: Discussionmentioning
confidence: 99%
“…In this same vein, additional complexity (e.g. adding microscopic sweat ducts [19,38]) may not change the relevant clinical parameters predicted by these models.…”
Section: Discussionmentioning
confidence: 99%
“…Insufficient dosing is another major limiting factor of tES due largely to anatomical and physiological differences across individuals 34,35 . Thicker layers of CSF and skull 36,37 , and a more resistive dermis 38,39 shunt more current away from the brain, causing field reductions of 100% or more across individuals at fixed doses 40 . These field fluctuations are further exacerbated by movement or misplacement of electrodes 41,42 .…”
Section: Introductionmentioning
confidence: 99%